Molecular Characterization of Leptospira spp. in Environmental Samples from North-Eastern Malaysia Revealed a Pathogenic Strain, Leptospira alstonii - Chan, Yean Yean; Azian, Harun; Nabilah, Ismail (Hindawi Publishing Corporation, 2016)
The presence of pathogenic Leptospira spp. in the environment poses threats to human health. The aim of this study was to detect and characterize Leptospira spp. from environmental samples. A total of 144 samples comprised of 72 soil and 72 water samples were collected from markets and recreational areas in a north-eastern state in Malaysia. Samples were cultured on Ellinghausen and McCullough modified by Johnson and Harris media. Leptospires were positive in 22.9% (n = 33) of the isolates. Based on partial sequences of 16S rRNA, a pathogenic leptospire, Leptospira alstonii (n = 1/33), was identified in 3% of the isolates followed by intermediate leptospire (L. wolffii, n = 1/33, and L. licerasiae, n = 7/33) and nonpathogenic leptospire, L. meyeri (n = 22/33) in 24.2% and 66.7%, respectively. This study demonstrates the presence of a clinically significant pathogenic L. alstonii in the environments which could pose health risks to the occupants and visitors.